Features of Recognizing Images of Figures of Different Colors and Sizes by Children 3-4 Years Old Using a Noise Background - T.G. Kuznetsova; M.L. Struzhkin; I.Yu. Golubeva (Moscow State University of Psychology and Education, 2024)
The study is aimed at analyzing the training of early preschool children to recognize visual stimuli of different colors and sizes, based on a method we are developing, in an ordinary situation and with the introduction of acoustic interference, i.e., spoken noise presented through headphones. The materials of two empirical studies on a sample of 3–4-year-old children (3.5±0.43) from a kindergarten in St. Petersburg, of whom there were 13 girls and 17 boys, are presented. The study was conducted with an interval of 2 months. The findings showed that children took longer to recognize and select stimuli of different colors and made more perseverative errors, compared to recognizing and selecting stimuli of different sizes. The introduction of acoustic noise significantly impaired task success, which was particularly pronounced when identifying irritants from colored stimuli. It is suggested that difficulties in identifying colored stimuli may be due to the absence of a sensory reference marked by a word, and the acoustic noise slowed sensorimotor response.